Perioperative Hemostatic Features in Patients with Acute Coronary Syndrome and Chronic Coronary Heart Disease - Yu. V. Nikiforov; G. G. Chernysheva; L. V. Molchanova; M. Ye. Yevdokimov (Общая реаниматология)
Objecive: to study and compare the time course of hemostatic changes in patients with acute coronary syndrome (ACS) and chronic coronary heart disease (CCHD) undergoing surgical myocardial revascularization.Subjects and methods. Eleven hemostatic parameters were determined at 3 study stages (before, within 24 hours after surgery and before hospital discharge) in 20 patients with CCHD and 23 with ACS.Results: The study demonstrated that there was a preponderance of a higher blood tendency to intravascular thrombogenesis in all the patients at all the stages of the study; however, the degree of disorders and the cases of their occurrence in the CCHD and ACS groups varied.Conclusion: There was an increased blood tendency to coagulation in all the patients despite the therapy performed. In the CCHD group, hemostatic disorders were, as before, more pronounced than those in the ACS group. These facts suggest that the reserve functional capacities of the hemostatic system become normal only a significant amount of time after elimination of thrombogenic change-causing agents.